Team of rivals the political genius of Abraham Lincoln - Goodwin, Doris Kearns; Thomas, Richard (New Delhi Penguin Books, 2005)
When the 1860 Republican National Convention chose Abraham Lincoln over three seasoned politicians, his rivals were shocked and humilated. Lincoln immediately went about mending fences by inviting them to join his cabinet. Historian Doris Kearns Godwin reveals how Lincoln brilliantly converted former political foes and used them to strengthen his presidency.
Subtitle from container.
Abridged.
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Friends and associates; Political leadership -- United States -- Case studies; Genius -- Case studies; Presidents -- United States -- Biography; United States -- Politics and government -- 1861-1865.